A SOC1-like gene MtSOC1a promotes flowering and primary stem elongation in Medicago. (26th July 2018) - Jaudal, Mauren; Zhang, Lulu; Che, Chong; Li, Guifen; Tang, Yuhong; Wen, Jiangqi; Mysore, Kirankumar S; Putterill, Joanna
Abstract : Overexpression of Medicago SOC1a leads to precocious primary shoot axis elongation. Abstract: Medicago flowering, like that of Arabidopsis, is promoted by vernalization and long days, but alternative mechanisms are predicted because Medicago lacks the key regulators CO and FLC. Three Medicago SOC1-like genes, including MtSOC1a, were previously implicated in flowering control, but no legume soc1 mutants with altered flowering were reported. Here, reverse transciption–quantitative PCR (RT–qPCR) indicated that the timing and magnitude of MtSOC1a expression was regulated by the flowering promoter FTa1, while in situ hybridization indicated that MtSOC1a expression increased in the shoot apical meristem during the floral transition. A Mtsoc1a mutant showed delayed flowering and short primary stems. Overexpression of MtSOC1a partially rescued the flowering of Mtsoc1a, but caused a dramatic increase in primary stem height, well before the transition to flowering. Internode cell length correlated with stem height, indicating that MtSOC1a promotes cell elongation in the primary stem. However, application of gibberellin (GA3 ) caused stem elongation in both the wild type and Mtsoc1a, indicating that the mutant was not defective in gibberellin responsiveness. These results indicate that MtSOC1a may function as a floral integrator gene and promotes primary stem elongation. Overall, this study suggests that apart from some conservation with the Arabidopsis flowering network, MtSOC1a has a novel role in regulating aspects of shoot architecture.